Buyer Uncertainty about Seller Capacity: Causes, Consequences, and a Partial Solution - John Horton (Center for Economic Studies and ifo Institute (CESifo), 2018)
Employers in an online labor market often pursue workers with little capacity to take on more work. The pursuit of low-capacity workers is consequential, as these workers are more likely to reject employer inquires, causing a reduction in the probability a job opening is ultimately filled. In an attempt to shift more employer attention to workers with greater capacity, the market-designing platform introduced a new signaling feature into the market. It was effective, in that when a worker signaled having high capacity, he or she received more invitations from employers, rejected a smaller fraction of those invitations, quoted a lower price to do the work, and was more likely to be hired. A back-of-the-envelope calculation suggests the signaling feature alone could increase market surplus by as much as 6%, both by increasing the number of matches formed and by helping to allocate projects to workers with lower costs.
Keywords: 330; labor economics; market design; digitization